خلافت عثمانیہ كے خاتمے پر مسلم ہندوستان كا ردِعمل ابوالکلام آزاد، علامہ محمد اقبال اور مولانا برکت اللہ بھوپالی: Response of Muslim India to the end of Ottoman Caliphate Abul Kalam Azad, Muhammad Iqbal, and Maulana Barkatullah Bhupali - Dr Shahid Rasheed (Al Manhal Research Journal, 2024)
This paper seeks to capture some of the most important responses from Muslim India to the and of Ottoman Caliphate. These responses are from Maulana Abul Kalam Azad, Dr. Muhammad Iqbal and Maulana Barkatullah Bhopali In 1924 when the caliphate was abolished, Indian Muslims were shocked. Allegiance to the caliphate had become the center of their religio-political worldview. They were upset by the tide of nationalist forces sweeping away the caliphate. Deputation was send to Turkey by the Khilafat Conference but to the utter dismay of Indian Muslims, the Turkish republic refused to receive the Indian delegation. A new kind of political consciousness developed in Muslim India after the Khilafat movement in which both Indian nationalism and Muslim nationalism flourished. Three major Muslim voices who tried to rebuild Muslim confidence have been discussed in this article.